The Principal of Madrasah Examplary to Improve Teacher performance at MIS Al Azhar Sido Makmur Labuhanbatu - Syawal Syawal (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
In essence, leaders have the ability to influence the behavior of others. This study aims to see how the School Principal's Examplary Leadership in Improving Teacher Performance at MIS Al-Azhar Sido Makmur, Labuhan Batu Regency. Descriptive analysis techniques through observation, interviews, and document studies. Data were obtained from several participants including the school principal ofmadrasa, the deputy head, 5 teachers, and 25 students. The results of the study has been able to give concrete examples to teachers in schools. It is considered as good exemplary leadership. Teacher performance which isseen from work performance among teachers already has strategies, teaching methods, has teaching competence and has a teaching plan and teachers are also responsible for the learning process. The head of the madrasah conducts ongoing evaluations in an effort to realize the vision and mission of education in schools so that they can anticipate various problems that may arise.